Unusually well-preserved fossil material dates the extant brittle star genus Actinozonella (Echinodermata: Ophiuroidea) to at least the Late Cretaceous - Stöhr, Sabine; Jagt, John W.m.; Thuy, Ben (Zootaxa, 2026)
Recent advances in molecular phylogenies have revolutionised our understanding of brittle star systematics and evolutionary history. Although genetic data have provided new grounds for age estimates of phylogenetic divergences, direct fossil evidence is currently the only robust means to determine the minimum age of clades. The present study discusses an exceptional opportunity to robustly pinpoint the minimum age of an extant genus of brittle star. The presumed ophiolepidid brittle star species Ophiolepis? falsa Jagt & Kutscher, in Jagt, 2000, from lower upper Campanian (Upper Cretaceous, c. 79 Ma) deposits in north-east Belgium, is here recorded from coeval strata in the Münsterland Basin (northern Germany) and transferred to the previously monospecific extant hemieuryalid genus Actinozonella Stöhr, 2011. An unusually well-preserved specimen, completely free from mineralised matrix, allows both dorsal and ventral sides of the disc and short arm stumps to be examined. In this way, characters not visible in the holotype of Ophiolepis? falsa could be analysed; these revealed its taxonomic affinity with Actinozonella, dating that genus to at least 79 Ma. The close morphological similarity between Actinozonella and Ophiomisidium Koehler, 1914, and to some species currently assigned to Ophiomastus Lyman, 1878, is discussed.